2010
DOI: 10.1128/jcm.01843-09
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive IgM Serology in Coccidioidomycosis

Abstract: The clinical observation has been made that there might be an unacceptable number of false-positive enzyme immunoassay (EIA) test results for IgM among persons suspected of having coccidioidomycosis. Patients with a positive result for IgM by EIA are thought to have a diagnosis of acute coccidioidomycosis. However, this study found that 82% of patients with an IgM-positive and IgG-negative EIA result did not have coccidioidomycosis.The Premier Coccidioides enzyme immunoassay (EIA; Meridian Bioscience, Inc., Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 5 publications
0
33
1
Order By: Relevance
“…In contrast, Kuberski et al identified 17 patients with positive EIA IgM and negative EIA IgG tests and determined that only 3 of them "may have had coccidioidomycosis," giving a false-positive rate of 82% (150). The inclusion/exclusion criteria were not specified, nor was it stated whether there was any additional serologic testing.…”
Section: Diagnostic Testing Serologymentioning
confidence: 99%
“…In contrast, Kuberski et al identified 17 patients with positive EIA IgM and negative EIA IgG tests and determined that only 3 of them "may have had coccidioidomycosis," giving a false-positive rate of 82% (150). The inclusion/exclusion criteria were not specified, nor was it stated whether there was any additional serologic testing.…”
Section: Diagnostic Testing Serologymentioning
confidence: 99%
“…Although the cases focus on virology due to the nature (4,5), Toxoplasma gondii (6)(7)(8), the Coccidioides spp. causing coccidiomycosis (9), and Borrelia burgdorferi (10).…”
mentioning
confidence: 99%
“…One retrospective study demonstrated that 86% of patients with this test result had positive serologic findings by other methods (5), a finding echoed in the present study of 102 patients, in which 80 (78%) had either positive culture or histology or positive serologic findings by other methods. The demonstration of both IgM and IgG by EIA has been repeatedly shown to correlate well with other diagnostic assays in reference laboratories (6,7,13), but the finding of the IgM ϩ /IgG Ϫ remains problematic. Such problems with the IgM resolve when the serology is repeated (5), and seroconversion from isolated EIA IgM reactivity to EIA IgG reactivity occurs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the EIA has generated some controversy, especially as it pertains to the particular finding of immunoglobulin M (IgM) reactivity in the absence of any immunoglobulin G (IgG) detected (EIA IgM ϩ /IgG Ϫ ). The few publications on this subject have been mixed: 1 study showed no falsepositive results on EIA IgM ϩ /IgG Ϫ for patients symptomatic for coccidioidomycosis (5), another demonstrated 2.2% (6), and a third study demonstrated an 82% false-positive rate (7). The finding of IgM reactivity in the absence of IgG by EIA is therefore difficult to interpret.…”
mentioning
confidence: 93%